STATELESS AND RIGHTLESS: The Human Rights Challenges of Rohingya Refugees in Thailand - Hitami, Munzir (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This article examines the human rights challenges faced by stateless Rohingya refugees in Thailand, a country that neither recognizes them as refugees nor offers pathways to legal protection. Treated as illegal migrants under Thailand’s 1979 Immigration Act, Rohingya are subject to indefinite detention, denial of due process, and systemic exclusion. Drawing on human rights reports, legal frameworks, and critical theory, this study analyzes how statelessness functions as both a legal and political condition, depriving individuals of recognition, rights, and recourse. Employing a theoretical framework that integrates statelessness theory (Arendt, Bhabha), international human rights law (Hathaway), and securitization discourse (Copenhagen School), the article argues that the Rohingya crisis in Thailand represents a form of structural and epistemic violence. It highlights the regional complicity in this marginalization, particularly ASEAN’s inaction driven by non-interference and security concerns. By shifting focus from Myanmar to regional host states, the article contributes to broader debates on statelessness, regional responsibility, and the limits of human rights enforcement in Southeast Asia. It concludes that without political recognition and legal reform, Rohingya in Thailand will remain permanently trapped between borders and beyond protection.